Moss Pathogenesis-Related-10 Protein Enhances Resistance to Pythium irregulare in Physcomitrella patens and Arabidopsis thaliana - Castro, Alexandra; Vidal, Sabina; Ponce de León, Inés (Frontiers in Plant Science, 2016)
Plants respond to pathogen infection by activating signaling pathways leading to the accumulation of proteins with diverse roles in defense. Here, we addressed the functional role of PpPR-10, a pathogenesis-related (PR)-10 gene, of the moss Physcomitrella patens, in response to biotic stress. PpPR-10 belongs to a multigene family and encodes a protein twice the usual size of PR-10 proteins due to the presence of two Bet v1 domains. Moss PR-10 genes are differentially regulated during development and inoculation with the fungal pathogen Botrytis cinerea. Specifically, PpPR-10 transcript levels increase significantly by treatments with elicitors of Pectobacterium carotovorum subsp. carotovorum, spores of B. cinerea, and the defense hormone salicylic acid. To characterize the role of PpPR-10 in plant defense against pathogens, we conducted overexpression analysis in P. patens and in Arabidopsis thaliana. We demonstrate that constitutive expression of PpPR-10 in moss tissues increased resistance against the oomycete Pythium irregulare. PpPR-10 overexpressing moss plants developed less symptoms and decreased mycelium growth than wild type plants. In addition, PpPR-10 overexpressing plants constitutively produced cell wall depositions in protonemal tissue. Ectopic expression of PpPR-10 in Arabidopsis resulted in increased resistance against P. irregulare as well, evidenced by smaller lesions and less cellular damage compared to wild type plants. These results indicate that PpPR-10 is functionally active in the defense against the pathogen P. irregulare, in both P. patens and Arabidopsis, two evolutionary distant plants. Thus, P. patens can serve as an interesting source of genes to improve resistance against pathogen infection in flowering plants.